THE EFFECT OF CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE AND PROFITABILITY ON FIRM VALUE (Survey on Pharmaceutical Industry Companies Listed on the IDX) - Majid, Dian Tresa; Ermanda, Annisa; Aisyah, Desy Nur; Padli, Ujang Darul; Abdulloh, Muhammad Afiev; Ikram, Syafrizal (CENTRAL ASIA AND THE CAUCASUS, 2022)
This study intends to examine how the influence of a disclosure of corporate social responsibility and profitability as a factor to increase firm value. The independent variable in this study is the disclosure of corporate social responsibility and profitability and the dependent variable is company value.This quantitative approach is the method used in this study with a sample population of companies in the pharmaceutical industry listed on the IDX in the period 2018-2020. Multiple linear regression analysis was used as data analysis with a significance level of 5% using IBM SPSS Statistics 26 as the data statistical analysis program. The results obtained in the study stated that there was an effect of corporate social responsibility disclosure on firm value and stated that there was no effect of profitability on firm value. Corporate social responsibility is an important part that involves the environment as a factor in increasing the value of the company. To increase profitability, the company must pay attention to the number of sales obtained. Companies can take advantage of the optimal use of assets so that an effective asset turnover can be obtained.